An overlooked plant–parakeet mutualism counteracts human overharvesting on an endangered tree - Speziale, Karina Lilian (2018)
The exponential growth of the human population often causes the overexploitation of resources and disruption of ecological interactions. Here, we propose that the antagonist effect of humans on exploited species might be alleviated with the advent of a second predator species. We focused on the complex interactions between an endangered conifer (Araucaria araucana) and two seed exploiters: the Austral parakeet (Enicognathus ferrugineus) and human seed collectors. We tested the importance of partial seed consumption by parakeets as an escape from human seed harvesting. Although parakeets frequently ate whole seeds, a substantial proportion of the seeds found under trees were only partially eaten and avoided by human seed collectors. These seeds germinated at a similar proportion but faster than intact seeds under laboratory conditions. Our results revealed an overlooked mutualism between parakeets and an endangered tree. Incomplete seed eating by parakeets, plus selection against these eaten seeds by humans, may enhance regeneration possibilities for this conifer species subject to human seed collection, turning the scale of the antagonism–mutualism continuum to the mutualistic side. In this context, parakeets might be providing an important service in those forests subject to human harvesting by allowing a fraction of seeds to escape human predation.